2011
DOI: 10.1021/mp200485b
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Intracellular Efficacy of Dextran-Histidine Polycation as an Efficient Nonviral Gene Delivery System

Abstract: In this study, we attempted to elucidate the capability of a natural polymer dextran, by modification with histidine, to be an efficient, safe and promising nucleic acid delivery system in gene therapy. Physicochemical characterizations were performed to get an insight into the derivative. The efficiency of the derivative as a gene delivery vehicle was also studied in depth using fluorescence microscopy. Extensive efforts were made to have a better understanding of the cellular dynamics involved. The derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Attaching amino acids to polysaccharides has been carried out by different approaches . On the contrary to previous studies relying on PEG spacers, in the present study the approach of directly coupling amino acids to dextran was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attaching amino acids to polysaccharides has been carried out by different approaches . On the contrary to previous studies relying on PEG spacers, in the present study the approach of directly coupling amino acids to dextran was used.…”
Section: Resultsmentioning
confidence: 99%
“…Attaching amino acids to polysaccharides has been carried out by different approaches. [40,41] On the contrary to previous studies relying on PEG spacers, in the present study the approach of directly coupling amino acids to dextran was used. To this end, the method of linking of the Boc-protected acid as an ester after activation with 1,1'-carbonyldiimidazole (CDI) was chosen.…”
Section: Synthesis and Characterization Of Boc-protected Amino Acid Ementioning
confidence: 99%
“…Additionally, augmented transfection efficiencies triggered by chloroquine, an endosomolytic reagent, also indicated that all NC would enter endo-lysosomal compartments once internalized (Fig. 6e) (31,32). Consequently, reduction or avoidance of endosomal entrapment was particularly important for successful gene transfection (33).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, and due to the fact that viral vectors, although possessing excellent transfection efficiency, are also toxic and may lead to immunogenicity problems, the use of polycationic macromolecules is an excellent alternative vehicle for nucleic acid drugs [104][105][106]. Inside this area, dextran derivatives have been frequently used [107][108][109][110] because of their beneficial features, as recently reviewed by Huang and Huang [93]. Finally, it is worth mentioning the use of dextran-hemoglobin conjugates as blood substitutes for patients suffering from asthma or other hemoglobin-compromised conditions.…”
Section: Dextranmentioning
confidence: 99%